1953
DOI: 10.1002/j.1538-7305.1953.tb01465.x
|View full text |Cite
|
Sign up to set email alerts
|

Cold Cathode Tubes for Transmission of Audio Frequency Signals

Abstract: Cold cathode gas filled tubes have been extensively applied as electronic switching elements in the telephone system. In general, these applications have been limited to control circuits. The usefulness of these tubes can be further extended by making them capable of carrying voice frequency signals. The transmission properties that are required of the tube for this use are considered. It is shown that troublesome oscillatory noise can be eliminated and that the insertion loss of the tube can be reduced to a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1956
1956
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…Tills relationship has already been found by Townsend and Depp (1953) at constant pressure. They also found that the resistance could be given by .Plot of reactance at 3 kc/s against the reciprocal of thc current.…”
Section: The Effect Of Currentmentioning
confidence: 70%
See 1 more Smart Citation
“…Tills relationship has already been found by Townsend and Depp (1953) at constant pressure. They also found that the resistance could be given by .Plot of reactance at 3 kc/s against the reciprocal of thc current.…”
Section: The Effect Of Currentmentioning
confidence: 70%
“…It ha~been suggested that the resistive component R],l is a function of the reciprocal of the pressure. Townsend and Depp (1953) whereas Benson and Bental (1955) found that the impedance of certain commercial tubes was given by…”
Section: The Effect Of Gas Pressurementioning
confidence: 96%
“…The existence of a region of negative differential resistance in the V -I characteristics of the double cathode cold discharge was already pointed out in the paper [13], while other works [l-l, 1.51 investigated this characteristic for a plane-parallel geometry in relation with the processes of cathode sputtering. The dotted lines represent the characteristics, as they would be 'expected for a usual abnormal discharge, without the double-cathode effect.…”
mentioning
confidence: 85%
“…The transition is accompanied by a marked increase in the discharge current for a given voltage. This phenomenon was first observed by Townsend in 1953 [1] and later was called 'hollow cathode effect' or 'hollow cathode mode' (HCM) [2]. Although HCM has been found for >60 years, many investigations on HCD are still performed [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%